Silicon carbide LED - Vlaskina, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Silicon carbide has been widely used as material for manufacturing yellow, red, green LED and optoelecronics devices (in¬dicators, screens). The silicon carbide LED technology has been in¬vestigated for improvement of their operational characteristics. This in¬cludes the influences of the surface processing (etching, annealing), the formation method for the p-n junctions and the contacts on the LED properties. Light-emitting devices used as light sources for optical-fiber communication lines. LED fabricated by Al⁺ ion-implanted in 6H-SiC and investigated their characteristics for an effective green LED. The brightness of the ion-implanted p-n junction was found to be two orders higher than that of diffusion p-n junction, and the best value was 2000-10000 cd/m² with passing current about 0.5 mA through area 50x50 mm and applied voltage about 2.6 ± 0.2 V. The ion-implanted structures showed a high stability of light in the temperature range of 77-600 K.